Inequality in Denmark through the Looking Glass - Causa, Orsetta (OECD Publishing, 2016)
This paper delivers a broad assessment of income inequality in Denmark. As a necessary preamble to provide a basis for discussion, we start by contrasting Danish official inequality measures with those gathered by the OECD in an international context. We show that differences between these two sources are fully explained by differences in methodological choices. We then go beyond synthetic measures of inequality to deliver a granular assessment of income distribution and of the distributional impact of taxes and transfers; and on this basis we compare Denmark to other OECD countries. This approach is then used to quantify the distributional impact of some growth-enhancing reforms undertaken or recommended for Denmark, based on empirical evidence across OECD countries. Finally, we take a forward looking stance by discussing global forces shaping the rise in inequality, in particular skill-biased technological change and deliver a tentative scenario for Denmark in the wider OECD context
Keywords: Economics; Denmark